Inhibition of heterocyclic amine formation in ground beef - B.G. Abdulkarim; J. Scott Smith (Kansas Agricultural Experiment Station Research Reports, 1999)
he natural antioxidant carnosine, moisture retention by covered cooking, and low temperature cooking were evaluated as ways to inhibit heterocyclic amine (HCA) formation in fried ground beef. Samples were fried at 375EF for 5 min/side, 300EF for 5 min/side, or 250EF for 8 min/side, with surface browning enhanced by applying a caramel solution (Maillose®) near the end of cooking times. Analysis for HCAs was performed on both the crust and the whole patties. Carnosine reduced 4,8-DiMelQx, a major HCA, to below its detection limit (.31 ng/g). HCAs were reduced when the cooking temperature was lowered from 375 to 300 or 250EF even with caramel applied on the surface. Cooking in a covered pan reduced levels of most HCAs but less than carnosine addition.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Ground beef; Heterocyclic Amine; Inhibition